A Pelatihan Konseling Pemberian Makan Anak Stunting Di Desa Melayu Timur Tahun 2023 - Farhat, Yasir; Pratiwi, Niken; Nurhamidi, Nurhamidi; Abdurrachim, Rijanti; Aprianti, Aprianti; Anwar, Rosihan; Mahpolah, Mahpolah (JURNAL RAKAT SEHAT (JRS) : Pengabdian Kepada Masyarakat, 2024)
Stunting or often called dwarf or short is a condition of growth failure in children under five years old (toddlers) due to chronic malnutrition and repeated infections, especially in the period of the First 1,000 Days of Life (HPK), namely from the fetus to the age of 2 years. The 1000 HPK period is also called the golden period as well as the critical period. This period is also closely related to the nutritional status of toddlers, the direct cause of nutritional problems is lack of nutritional intake and infectious diseases. Nutritional intake in the 1000 HPK cannot be separated from the Infant and Child Feeding Standards (PMBA). Reducing stunting rates by providing counseling on providing food for stunted children, by providing counseling on providing food for stunted children and providing food for children according to age. The methods implemented in this activity are training in counseling on providing food for stunted children and assistance in counseling on providing food for stunted children. The results of statistical tests with the Wilcoxon difference test showed that there was a significant difference (r=0,00) in the change in knowledge. Recommendations for training for motivational agents and training in other locations so that motivator groups can be formed in each fostered area.